Epidermodysplasia Verruciformis: A Clinicopathologic Review of Two Cases - Tummidi Santosh; Tanya Sharma; Deepti Joshi; Dinesh Prasad Asati; Sanjeev Vijay Choudhary; Neelkamal Kapoor (Clinical Dermatology Review)
Epidermodysplasia verruciformis (EV) is a rare autosomal recessive disease involving the immune system. It presents as pityriasis versicolor-like or warty papules, the onset being from early childhood at the face, dorsum of hands and feet. It can also occur as an acquired entity in patients with immunocompromised status, human immunodeficiency virus (HIV) infection, and immunosuppressant therapy. Hereby, we report two cases of EV, histologically diagnosed on skin punch biopsy, both presented with a clinical history of macular/verrucous lesions in various sun-exposed body regions. One of the cases was diagnosed with squamous cell carcinoma (SCC) in situ from the lesion on the left forehead. EV is associated with beta-human papillomavirus infection and later the progression to malignancy. Early detection and preventive measures can help in the progression of the disease to Bowen’s disease or invasive SCC.